Comprehensive Insights Into E-Learning in Contemporary Education: Analyzing Trends, Challenges, and Best Practices - Musawer Hakimi; Shairagha Katebzadah; Abdul Wajid Fazil (CV. Pusdikra Mitra Jaya, 2024)
This study explores E-Learning in Modern Education at Afghanistan Universities, aiming to analyze trends, address challenges, and identify best practices. Employing a mixed-methods approach, it incorporates surveys and content analysis for both quantitative and qualitative data. A stratified random sampling strategy ensures representation from diverse faculties, resulting in 180 participants. Key findings emphasize widespread adoption of Learning Management Systems, multimedia content, mobile learning, and gamification for enhanced student engagement. Challenges include content management and resistance to change, highlighting complexities in E-Learning implementations. The study aligns with established theoretical frameworks like the Technology Acceptance Model and cognitive load theory, contributing to the theoretical understanding of E-Learning dynamics. Implications extend to educators, policymakers, and instructional designers, guiding strategic decision-making and interventions. Limitations, including potential response bias and context-specific considerations, underscore the need for cautious interpretation, paving the way for future research. In conclusion, this research provides a comprehensive examination of E-Learning trends and challenges, offering actionable insights for the ongoing discourse in digital education.